Study on the Matrix Solid-Phase Dispersion and GC/MS for the Determination of Pesticides in Tobacco - Wang, Lan; Chzn, Yong-Kuang; Liao, Zhen; Chen, Zhang-Yu; Jiang, Ci-Qing; Yang, Guang-Yu (Asian Journal of Chemistry, 2010)
In this study, a new method for the matrix solid-phase dispersion and gas chromatography-mass spectrometry (GC/MS) determination of pesticides in tobacco was established. The tobacco samples were blended into the graphitized carbon black with a glass pestle and introduced into a polypropylene cartridge. Then, the pesticides were eluated from the homogeneous mixture with methanol as eluant. The pesticides (acephate, chlorpropham, pirimicarb, bifenthrin, tetradifon and phosalone) were determination by GC/MS with selected ion monitoring (GC/MS, SIM). The recoveries of this method were ranging from 88-96 % with relative standard deviations of 3.8-5.2 %. The detection limits were ranged from 0.05-0.10 mg kg-1, respectively, for the different pesticides studied.